2017
DOI: 10.1021/acs.biomac.7b01175
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformation of Polymer Brushes Determines Their Interactions with DNA and Transfection Efficiency

Abstract: Polymer brush-functionalized nanomaterials offer interesting features for the design of gene delivery vectors as their physicochemical and structural properties can be designed independently of the chemistry, size and shape of the nanomaterial core. However, little is known of the parameters regulating the adsorption and infiltration of DNA molecules at the surface of positively charged polymer brushes, despite the importance of such processes for gene delivery. Here we investigate the role of the molecular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 63 publications
6
47
0
1
Order By: Relevance
“…12 Recently, the high grafting density of positively charged polymer brushes has been shown to enable the highstability binding of oligonucleotides, making these brushes quite promising for gene and small RNA (siRNA and miRNA) delivery. 13,14 Cationic polymer brushes such as poly(dimethyl aminoethyl methacrylate) (PDMAEMA) have shown the potential to capture oligonucleotides, in particular small RNAs relevant for siRNA and miRNA delivery. 14 It was further observed that RNA interactions, specifically with oligonucleotides ranging in size between 20 and 30 base pairs, are more stable than corresponding DNA molecules of similar sizes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Recently, the high grafting density of positively charged polymer brushes has been shown to enable the highstability binding of oligonucleotides, making these brushes quite promising for gene and small RNA (siRNA and miRNA) delivery. 13,14 Cationic polymer brushes such as poly(dimethyl aminoethyl methacrylate) (PDMAEMA) have shown the potential to capture oligonucleotides, in particular small RNAs relevant for siRNA and miRNA delivery. 14 It was further observed that RNA interactions, specifically with oligonucleotides ranging in size between 20 and 30 base pairs, are more stable than corresponding DNA molecules of similar sizes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tethering a chloro-and alkoxy-silane functionalized initiators to an oxidized silicon sub-strate is the most frequently applied route for the generation of polymer brushes via SI-CRP. This strategy is routinely used for the functionalization of a wide range of surfaces, including glass, quartz, [34] porous, [19,35] and nonporous silica particles, [18,36] as well as other nanoparticles displaying a silica shell (e.g., Fe 3 O 4 /silica nanoparticles [37] ). Noncovalent adsorption of polyelectrolyte macroinitiators (e.g., cationic trimethylammoniumbased macroinitiator and anionic sulfate-based macroinitiator) has also demonstrated the capability of modification of silicon oxide surfaces and efficient initiation polymerization.…”
Section: Grafting Responsive Polymer Brushes From Various Substrates mentioning
confidence: 99%
“…For example, PDMAEMA with pendant tertiary amines is a temperature-and pH-responsive polymer, often used as cationic antibacterial surfaces and nonviral gene carriers for biomedical applications. [18,36,94,95] Many other responsive polymer brushes have been developed for use in drug delivery. We have summarized recent advances toward these applications in Table 1.…”
Section: Triggered Drug Delivery and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A adsorção de RNA com comprimento entre 20 and 30 bases é mais estável do que observado para moléculas de DNA de dimensões similares. 2,3 As bases moleculares desta preferência não são conhecidas. O presente trabalho tem como objetivo investigar estes processos.…”
Section: Introductionunclassified